Better prognostic accuracy in younger mild cognitive impairment patients with more years of education. Issue 1 (7th June 2018) - Göthlin, Mattias; Eckerström, Marie; Rolstad, Sindre; Kettunen, Petronella; Wallin, Anders
Abstract: Introduction: Age and years of education influence the risk of dementia and may impact the prognostic accuracy of mild cognitive impairment subtypes. Methods: Memory clinic patients without dementia (N = 358, age 64.0 ± 7.9) were stratified into four groups based on years of age (≤64 and ≥65) and education (≤12 and ≥13), examined with a neuropsychological test battery at baseline and followed up after 2 years. Results: The prognostic accuracy of amnestic multi‐domain mild cognitive impairment for dementia was highest in younger patients with more years of education and lowest in older patients with fewer years of education. Conversely, conversion rates to dementia were lowest in younger patients with more years of education and highest in older patients with fewer years of education. Discussion: Mild cognitive impairment subtypes and demographic information should be combined to increase the accuracy of prognoses for dementia. Highlights: Lowest conversion rate to dementia in younger patients with more years of education. Highest prognostic accuracy in younger patients with more years of education. Only amnestic multi‐domain MCI significantly predicted conversion to dementia.